Lifetime and 12‐Month Nonsuicidal Self‐Injury and Academic Performance in College Freshmen. Issue 5 (8th March 2016) - Kiekens, Glenn; Claes, Laurence; Demyttenaere, Koen; Auerbach, Randy P.; Green, Jennifer G.; Kessler, Ronald C.; Mortier, Philippe; Nock, Matthew K.; Bruffaerts, Ronny
Abstract : We examined whether nonsuicidal self‐injury (NSSI) is associated with academic performance in college freshmen, using census‐based web surveys ( N = 7, 527; response = 65.4%). NSSI was assessed with items from the Self‐Injurious Thoughts and Behaviors Interview and subsequently linked with the administratively recorded academic year percentage (AYP). Freshmen with lifetime and 12‐month NSSI showed a reduction in AYP of 3.4% and 5.9%, respectively. The college environment was found to moderate the effect of 12‐month NSSI, with more strongly reduced AYPs in departments with higher‐than‐average mean departmental AYPs. The findings suggest that overall stress and test anxiety are underlying processes between NSSI membership and academic performance.